P68 Improving the management of chlamydia in non-GUM settings: it to the rescue!. (23rd May 2012) - Zhou, C N C; Roberts, J; Davies, J; Longbone, M; Dean, G
Abstract : Background: BASHH guidelines recommend all patients diagnosed with Chlamydia trachomatis (CT) should be given a detailed explanation of the condition, managed with appropriate antibiotics and have effective partner notification (PN). Patients tested in non-GUM settings may receive sub-optimal management. Following a 2008 audit highlighting several untreated CT cases in the Gynaecology Department (GD) we introduced a bespoke IT lab-link allowing daily downloads of results to GUM health advisers (HA). Objectives: To re-audit the management of females tested for CT in GD. Methods: We performed a retrospective database analysis of all CT tests requested by any of the 11 Gynaecology consultants from June 11 to January 12. Demographic and clinical details were extracted from a prospectively collected lab. database and clinic records. Results were compared with the 2008 audit. Fisher's exact test was used to compare differences between proportions. Results: 889 tests 864 (97.2%) negative, 16 (1.8%) positive, 9 (1%) not tested—incorrect swab were requested by GD over 29 weeks. HAs were notified of 100% of results in real time. Median time from notification of positive results to patient contact was 1 day (range 1–60). Median time from positive result to treatment was 7 days (range 1–70). This compares to an upper limit of 168 days in the 2008 audit. Recommended antibiotics were used in all cases. PN outcomes improved from 31% to 75% (p=0.02) and untreated cases decreased from 38% to 18.7% (p=0.2) (see abstract P68 table 1 ). Discussion: Since the introduction of a referral pathway and automated IT lab-link, management of CT positive patients from GD has improved, in particular PN and proportion left untreated. GUM departments should have a clear pathway for the management of patients diagnosed with STIs in non-GUM settings.